Identification of tigecycline- and vancomycin-resistant Staphylococcus aureus strains among patients with urinary tract infection in Iran. (September 2017) - Yousefi, M.; Fallah, F.; Arshadi, M.; Pourmand, M.R.; Hashemi, A.; Pourmand, G.
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the major causes of hospital- and community-acquired infections worldwide. Although S. aureus rarely accounts for urinary tract infections (UTI), untreated UTI can lead to several complications. For decades vancomycin has been used for the treatment of MRSA infections. This study was performed to assess the in vitro activity of vancomycin, tigecycline, linezolid and quinupristin/dalfopristin against MRSA isolates from UTI patients. Thirty MRSA strains from 54 S. aureus isolates were isolated from patients with UTI. The antimicrobial susceptibility patterns of the strains were determined by the Kirby-Bauer disk diffusion and broth microdilution methods. PCR assays were used to detect the van A gene. The MRSA isolates resistant to vancomycin were confirmed using the broth microdilution method. The results revealed that the MRSA isolates were 100% susceptible to linezolid and quinupristin/dalfopristin but 93.3% susceptible to vancomycin and tigecycline respectively. The broth microdilution method confirmed two MRSA strains (6.6%) to be resistant to vancomycin and tigecycline. The study identified vancomycin resistance among the MRSA isolates from UTI patients. This vancomycin resistance in MRSA isolates poses a challenge in managing S. aureus infections. Our study's results highlight the need to correctly identify patients in whom last-resort therapy such as linezolid and quinupristin/dalfopristin should be administered.